2021
DOI: 10.1111/bdi.13067
|View full text |Cite
|
Sign up to set email alerts
|

Can network analysis of self‐reported psychopathology shed light on the core phenomenology of bipolar disorders in adolescents and young adults?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Second, increased physical activity at 19Up was associated with an increased likelihood of progression to a hypo-manic-like subthreshold syndrome. This finding is consistent with a recent network analysis at a single timepoint in BLTS showing that increased physical activity was an influential node among youth with recent-onset bipolar disorder [23]. Another study showed that subsyndromal manic symptoms were associated with a new-onset bipolar spectrum disorder among youth at familial risk of bipolar disorder [42].…”
Section: Primary Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…Second, increased physical activity at 19Up was associated with an increased likelihood of progression to a hypo-manic-like subthreshold syndrome. This finding is consistent with a recent network analysis at a single timepoint in BLTS showing that increased physical activity was an influential node among youth with recent-onset bipolar disorder [23]. Another study showed that subsyndromal manic symptoms were associated with a new-onset bipolar spectrum disorder among youth at familial risk of bipolar disorder [42].…”
Section: Primary Findingssupporting
confidence: 90%
“…The 12-item Somatic and Psychological Health Report (SPHERE-12) measured the presence/absence of somatic (SOMA-6 subscale, e.g., hypersomnia, anergia) and anxious-depressive symptoms (PSYCH-6 subscale, e.g., feeling overwhelmed, hopelessness) over recent weeks [27]. Five hypo-manic symptoms (persistence >2 days of, e.g., decreased need for sleep, feeling elated) were examined using an investigator-devised self-rating scale (used in several of our studies) [23, 24, 28]. Six psychotic-like symptoms (e.g., auditory hallucinations) were assessed using a tool adapted in part from the Community Assessment of Psychic Experiences [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, even though two previous studies included psychomotor speed in their networks (both revealing that it was central in mania/bipolar disorder), one of them conceptualized such speed in terms of goal-directed activity, 51 whereas the other one did so in terms of speed of speech. 52 Other differences may also be expected, given underlying population differences. For example, 'talkativeness' and 'thinking faster' were consistently shown to be central facets of hypomanic symptoms, 18 distinguish individuals with bipolar disorder type II from those with type I, 19 and, finally, be central facets to individuals with a bipolar diagnosis, who are minimally impaired.…”
Section: Discussionmentioning
confidence: 99%
“…The node strength is the most commonly used indicator of centrality. It is the sum of all edge weights connected to the node [15, 28, 29]. Moreover, the node predictability was calculated.…”
Section: Methodsmentioning
confidence: 99%